Anti-bullying Awareness of High School Students in Yogyakarta City - Rahmawati, Dila; Suwarjo, Suwarjo; Rertnawati, Heri (Psikopedagogia, 2021)
This study aims to determine the anti-bullying awareness of high school students in Yogyakarta City. This research is a phenomenological type of qualitative research. The data in this study were collected through interview instrument guidelines and observation guidelines. The subjects in this study were 25 students from six different schools in Yogyakarta City. The study used data analysis by Miles and Huberman. The results of the study show that anti-bullying awareness among high school students in Yogyakarta City is good. This is evidenced by: 1) well-known definitions of bullying, forms of bullying, and the impact of bullying, both victims and perpetrators; 2) broad insight based on the experience of being a victim of bullying, seeing bullying behavior directly or indirectly, and initiatives to help victims of bullying; 3) no desire to bully friends; 4) the ability to make friends by keeping feelings for each other and still upholding the prevailing norms. The results of the study can be used as a reference for guidance and counseling teachers or counselors to design guidance and counseling services about bullying to prevent bullying in high school students in Yogyakarta City.